In vitro comparison of NiTi rotary instruments and stainless steel hand instruments in root canal preparations of primary and permanent molar - Nagaratna P; Shashikiran N; Subbareddy V (Wolters Kluwer Medknow Publications, 2006)
This study is an attempt to compare the NiTi rotary and K-files hand instrumentation on root canal preparation of primary and permanent molars for their efficiency in preparation time, instrument failure and shaping the canals. About 20 primary mandibular second molar (I) and 20 permanent mandibular first molar (II) were selected. Each was further divided into 10 for K-files (a) and 10 for NiTi (b) groups, respectively. Results showed that preparation time Ib<Ia and IIab<IIa, which was highly significant. In instrument failure, Ia (40%), IIa (30%) showed more deformation but not fracture and Ib (10%), IIb (20%) showed fracture, but not deformation. Profiles showed good canal taper and smoothness compared to the K-files. To conclude profile 0.04 taper 29 series, prepared canal rapidly than conventional K-file with good taper, smoothness though the flow was not satisfactory. Instrument failure with K-files was less. In primary teeth preparation time, instrument failure with profile was less compared to the permanent. To conclude it′s encouraging to use the profiles in primary teeth.